2006
DOI: 10.1111/j.1365-2133.1995.tb02738.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical stratum corneum lipids accelerate barrier repair after tape stripping, solvent treatment and some but not all types of detergent treatment

Abstract: Summary Topical act‐tone treatment extracts lipids from the stratum corneum. and disrupts the permeability barrier, resulting in a homeostatic response in the viable epidermis that ultimately repairs the barrier. Recently, we have developed an optimal lipid mixture (cholesterol, ceramide. palmitate and linoleate 4–3:2.3:1:1.08) that, when applied topically, accelerates barrier repair following extensive disruption of the barrier by acetone. The present study determined if topical treatment with this opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
83
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(85 citation statements)
references
References 18 publications
2
83
0
Order By: Relevance
“…When one topically applies a lipid mixture containing equimolar concentrations of all three essential lipids, permeability barrier recovery after acute disruption is normal (128)(129)(130). In contrast, topical application of any one or two of the three key lipids to acutely perturbed skin actually results in a delay in permeability barrier repair associated with abnormal-appearing lamellar bodies (128)(129)(130).…”
Section: Jlr: Are the Relative Quantities Of The Key Lipids Important?mentioning
confidence: 99%
See 2 more Smart Citations
“…When one topically applies a lipid mixture containing equimolar concentrations of all three essential lipids, permeability barrier recovery after acute disruption is normal (128)(129)(130). In contrast, topical application of any one or two of the three key lipids to acutely perturbed skin actually results in a delay in permeability barrier repair associated with abnormal-appearing lamellar bodies (128)(129)(130).…”
Section: Jlr: Are the Relative Quantities Of The Key Lipids Important?mentioning
confidence: 99%
“…In contrast, topical application of any one or two of the three key lipids to acutely perturbed skin actually results in a delay in permeability barrier repair associated with abnormal-appearing lamellar bodies (128)(129)(130). Both complete and incomplete mixtures of the three key lipids rapidly traverse the stratum corneum and are taken up by stratum granulosum cells, thereby markedly altering the molar distribution of lipids, leading to abnormalities in the formation of lamellar bodies (128)(129)(130). Along similar lines, chronic topical treatment with statins also results in abnormalities in lamellar body structure and permeability barrier homeostasis (57,131).…”
Section: Jlr: Are the Relative Quantities Of The Key Lipids Important?mentioning
confidence: 99%
See 1 more Smart Citation
“…1) Application of a SPT inhibitor to the skin disrupted by tape-stripping or acetone treatment showed a marked delay in the recovery of SC barrier function. 2,3) We previously reported that application of ISP-I to UVB-irradiated mouse dorsal skin decreased TEWL, despite the fact that ISP-I inhibits SPT and ceramide synthesis, which suggested that this phenomenon may be due to an increase in the number of SC layers in ISP-I-treated skin. 10) To date, no study is available regarding the effects of SPT modification on intact skin, as work has been limited to tape-stripped, acetone-treated, or UVB-irradiated skin.…”
Section: Fig 2 the Effect Of Isp-i Treatment On Skin Hydrationmentioning
confidence: 99%
“…Therefore, SPT is considered a key enzyme in the regulation of sphingolipid levels involved in ceramide production and it affects the epidermal barrier function. Holleran et al 2) and Yang et al 3) demonstrated that the application of a SPT inhibitor resulted in the delayed barrier recovery of mouse skin disrupted by tape-stripping and acetone treatment. However, the effect of SPT inhibition on SC barrier function in the intact skin has not yet been elucidated.…”
mentioning
confidence: 99%